Pengaruh Kondisi Laba Operasional Terhadap Manajemen Laba - Ivan Hadriyanto; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to identify and to prove the existence of the affects of conditions that decreased operating income toward the increasing in the earnings management activity by income maximization measured by using the modified Jones discretionary accrual models. The operating income condition measured by comparing the difference between operating income in year t minus operating income year t-1 divided by operating income in year t-1. Earnings management that occurred between the management company as agent and investor as principal measured by the modified Jones models.                                                      This study used the control variables, of firm size, market - to - book value ratio, and earnings per share. The research was conducted on public companies inIndonesialisted in LQ45 index by the calculation that had positive earnings management with a sample of 63 observations. The results showed that there was influence between the condition of operating income and earnings management. The results also showed that the earnings per share significantly influenced the earnings management, while firm size and market - to - book value ratio have no significant influence towards earnings management.